2023
DOI: 10.1021/acsnano.3c05510
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Surface-Enhanced Raman Spectra with a Raman Library Using Machine Learning

Yilong Ju,
Oara Neumann,
Mary Bajomo
et al.

Abstract: Since its discovery, surface-enhanced Raman spectroscopy (SERS) has shown outstanding promise of identifying trace amounts of unknown molecules in rapid, portable formats. However, the many different types of nanoparticles or nanostructured metallic SERS substrates created over the past few decades show substantial variability in the SERS spectra they provide. These inconsistencies have even raised speculation that substrate-specific SERS spectral libraries must be compiled for practical use of this type of sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 67 publications
0
1
0
Order By: Relevance
“…The obtained SERS spectra cannot be directly compared to Raman spectra. 54 This deserves further investigation. Second, the PFAS molecules still have low affinity to any substrates presented in this work, which was suggested by the concentration-dependent…”
Section: Discussionmentioning
confidence: 91%
“…The obtained SERS spectra cannot be directly compared to Raman spectra. 54 This deserves further investigation. Second, the PFAS molecules still have low affinity to any substrates presented in this work, which was suggested by the concentration-dependent…”
Section: Discussionmentioning
confidence: 91%
“…In addition to EC-SERS, we anticipate that advances in machine learning for spectral analysis and classification will further expand the capabilities of SERS , and other tools in nanoscience to increasingly complex samples and problems in conservation. For example, we recently demonstrated that several artists’ colorants (i.e., rhodamine and anthraquinone dyes) can be classified with machine learningdown to the single-molecule detection limitusing their intrinsic fluorescence dynamics .…”
Section: Why Sers Shines For Painting Analysismentioning
confidence: 99%
“…77,120–124 Such a collection of spectra under a large set of (relevant) experimental conditions would yield a ‘profile’ of a particular type of molecule that would allow its robust recognition in a multitude of interactions with a SERS substrate. 120,125,126…”
Section: Retrieving Meaningful Information From Sers Microspectramentioning
confidence: 99%